GMJ 2019
DOI: 10.31661/gmj.v8i0.1389
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a Persian Herbal Remedy and Electroacupuncture on Metabolic Profiles and Anthropometric Parameters in Women with Polycystic Ovary Syndrome: A Randomized Controlled Trial

Abstract: Background: The most prevalent endocrine disorder in women of reproductive age is polycystic ovary syndrome (PCOS). The purpose of this study was to evaluate the efficaciousness of a Persian herbal remedy, as well as electroacupuncture and the combination of them on metabolic profiles and anthropometric parameters in these patients. Materials and Methods: Eighty overweight women with PCOS were randomly divided into four groups. All of them received metformin 1000 mg and the second group received 5 g of herbal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…Abdominal acupuncture also improved insulin resistance in patients with obesity-type PCOS, which may be related to the efficacy of acupuncture treatment on body–mass index, waist-to-hip ratio (WHR), and lipid metabolism dysfunctions ( 43 ). Consistent with this study, EA was found to be effective in improving insulin resistance, as well as decreasing WHR and the levels of total cholesterol and low-density lipoprotein (LDL) cholesterol ( 54 , 62 ). EA was also reported to attenuate insulin resistance by inactivating the mTOR/4E-BP1 signaling pathway in a rat model of PCOS ( 12 ).…”
Section: Potential Mechanisms Of Acupuncture Affecting Pcos-related S...supporting
confidence: 77%
“…Abdominal acupuncture also improved insulin resistance in patients with obesity-type PCOS, which may be related to the efficacy of acupuncture treatment on body–mass index, waist-to-hip ratio (WHR), and lipid metabolism dysfunctions ( 43 ). Consistent with this study, EA was found to be effective in improving insulin resistance, as well as decreasing WHR and the levels of total cholesterol and low-density lipoprotein (LDL) cholesterol ( 54 , 62 ). EA was also reported to attenuate insulin resistance by inactivating the mTOR/4E-BP1 signaling pathway in a rat model of PCOS ( 12 ).…”
Section: Potential Mechanisms Of Acupuncture Affecting Pcos-related S...supporting
confidence: 77%
“…Rouhani et al [28] reported that in the group who received metformin + electroacupuncture + herbal medicine showed the greatest decrease in body fat and BMI compared with the groups receiving metformin only, metformin + electroacupuncture group and metformin + electroacupuncture + herbal medicine group. High density lipoprotein and low-density lipoprotein decreased in the metformin + electroacupuncture group, and metformin + electroacupuncture + herbal medicine group so it was judged that the combination treatment with acupuncture and oriental medicine treatment could treat metabolic complications and overweight problems better than metformin alone.…”
Section: Discussionmentioning
confidence: 99%
“… Increase of menstrual bleeding. ↑Menstrual cyclicity [ 91 ] Decoction Persian herbal remedy Foeniculum vulgare, Urtica dioica, Daucus carota, Trifolium pratense, Curcuman longa 80 overweight women with PCOS 5 g/day; 12 weeks Reduction of PCOS risk ↓TC, LDL-C, TG, AST, ALT, HDL-C, [ 92 ] Decoction Shouwu Jiangqi Decoction Fallopia multiflora, Radix puerariae, Batryticated silkworm, Astragalus propinquus Schischkin, Dioscorea oppositifolia L ., Euonymus alatus, Cyperus rotundus L ., Cuscutae semen. 81 participants diagnosed with PCOS, aged 18-35 3 months The expectation of efficacy of SWJQD on the treatment of PCOS with kidney deficiency, phlegm, and blood stasis ↑Insulin sensitivity [ 93 ] Decoction Yijin-tang Pinellia ternata Breitenbach, Citrus unshiu Markovich, Poria cocos Wolf, Glycyrrhiza uralensis Fisch, Zingiber officinale Roscoe 15 PCOS women with oligomenorrhea 6 g; 12 weeks Decrease in the menstrual cycle and follicle number.…”
Section: The Promising Evidence Of Natural Products In Modern Drug Di...mentioning
confidence: 99%
“…Rouhani et al revealed that Persian herbal remedies and electroacupuncture could be used as a better treatment of metabolic complications and overweight problems in patients with polycystic ovary syndrome [ 92 ]. Eighty overweight women with PCOS were randomly divided into four groups, the first group received metformin, the second group received metformin and Persian herbal remedy, the third group received metformin and electroacupuncture, and the fourth group received both therapies.…”
Section: The Promising Evidence Of Natural Products In Modern Drug Di...mentioning
confidence: 99%
See 1 more Smart Citation